The Role of Nonverbal Communication in People with Disabilities in the Socialization of SP4N LAPOR! in Banjarbaru City - Liliana, Gina; Novianti, Lieta Dwi; Aulia, Riska Noor (Magister Administrasi Bisnis ULM, 2024)
Abstract: SP4N LAPOR! is the first social media application in Indonesia that involves public participation and is two-way, so that in this application the public can interact with the government interactively. with the principle of easy and integrated for monitoring development and public services and researchers strive to bridge public participation between people with disabilities in Banjarbaru City and the South Kalimantan Provincial Government. Nonverbal communication for people with disabilities in the socialization of Sp4n LAPOR! in Banjarbaru City with the sub-issue of whether all SP4N LAPOR! platforms have been audited for accessibility for various disabilities and what has been reported regarding public services for people with disabilities in Banjarbaru City. Keywords: SP4N LAPOR!, Social Media, Public Service, Education, Digital Literacy